Democratic coexistence in students from the non-school program - Ponce-Vega, Cristina (2021)
In any research process, as we know, the scientific method allows us to detect problems and set objectives. Precisely, the study carried out, by the logical sense of educational research, starts by formulating an objective, based on the problem we determined, it was raised with the following statement: Establish the characteristics of democratic coexistence in the Students of the Non-School Program of the town of Los Ángeles, Tournavista, Puerto Inca 2020. The appropriate method was the analysis that allowed us to understand the texts included in the study. The result was; The correlation index shows that the value of r = 0.69 and r = 0.81, are located in the interval 0.40 ≤ r <0.80 and its interpretation indicates that there is a significant relationship between the theoretical characteristics of democratic coexistence and the practice of behavior of democratic coexistence in the Students of the Non-School Program of the town of Los Angeles, Tournavista, Puerto Inca 2020. Consequently, we have: It was established that there is a significant relationship between the theoretical characteristics of democratic coexistence and the practice of the behavior of Democratic coexistence, It was evidenced that there is a significant relationship between the characteristics of democratic coexistence with the ability to interact with all people, It was proven that there is a significant relationship between the characteristics of democratic coexistence with the management of conflicts in a constructive and it was stated that there is a significant relationship between the characteristics of e democratic coexistence with participation in actions that promote common welfare in the Students of the Non-School Program of the town of Los Angeles, Tournavista, Puerto Inca 2020.